24.1: Invited Paper: Design Principles for Light Field Image Capture and Display. Issue 1 (June 2015) - Berkner, Kathrin; Toši, Ivana; Wu, Wanmin; Meng, Lingfei; Bedard, Noah; Balram, Nikhil
Abstract : Light field capture and display technologies have been rapidly emerging in the past decade. The high dimensional design space of light field systems, however, imposes new challenges for end to end system design and evaluation. We discuss design principles for task specific light field camera systems and outline how such principles can be applied to or need to be modified for the design of personal light field displays.